On the Predictability of Growth - Cristelli, Matthieu; Tacchella, Andrea; Cader, Masud; Roster, Kirstin; Pietronero, Luciano (World Bank, Washington, DC, 2017)
A country's productive structure and competitiveness are harbingers of growth. Growth is a dynamic process based on capabilities that are difficult to define and measure across countries. This paper uses a global measure of fitness (or complexity-weighted diversity of production) as a method to explore a country's relative growth potential. The analysis finds that there are two types of growth, predictable or laminar, and unpredictable. This classification is used to create a selection mechanism (the Selective Predictability Scheme), defining future growth trajectories for similar countries, and compares projected long-term, five-year forecasts with traditional methods used by the International Monetary Fund. The analysis finds that production structure is a good long-term predictor of growth, with prediction performance falling off for countries not yet in the laminar classification.